MicroRNAs, polyamines, and the activities antioxidant enzymes are associated with in vitro rooting in white pine (Pinus strobus L.) - Fei, Yunjun (Springerplus, 2016)
Molecular mechanism of in vitro rooting in conifer is not fully understood. After establishment of a regeneration procedure in eastern white pine (Pinus strobus L.) using mature embryos as explants to induce shoot formation on medium containing 3 μM IAA, 6 μM BA and 6 μM TDZ and induce root formation on medium containing 0.001-0.05 μM IAA, 0.001–0.05 μM IBA, 0.001–0.05 μM TDZ, we have investigated the changes of polyamine content and the activities of antioxidant enzymes during in vitro rooting in P. strobus. Our results demonstrated that putrescine (Put), spermidine (Spd), and spermine (Spm) did not increase in P. strobus during the first week of rooting on medium supplemented with 0.01 μM indole-3-acetic acid (IAA), whereas the levels of Put, Spd, and Spm increased during the 1st–3rd week of culture on medium with IAA, and then decreased on medium with IAA. No such a change in Put, Spd, and Spm was observed on medium without IAA. Measurement of antioxidant enzyme activity demonstrated that the activities of polyphenol oxidase, catalase, and peroxidase slightly increased in the first week of culture and reached to the highest peak in the 3rd–5th week of culture. Quantitative RT-PCR results indicated that miR160 was increased on the 7th day, miR162, miR397, and miR408 was increased from the 21th to 35th day, miR857 was increased on the 35th day, and miR827 was increased on the 49th day. These results demonstrated that enhanced polyamine biosynthesis, antioxidant enzyme activity, and microRNAs are correlated with the root induction and formation in P. strobus.